Foxp3 expression in CD4+ T cells of patients with systemic lupus erythematosus: a comparative phenotypic analysis. Issue 5 (29th August 2007) - Bonelli, M; von Dalwigk, K; Savitskaya, A; Smolen, J S; Scheinecker, C
Abstract : Objectives: The forkhead family transcription factor Foxp3 currently represents the most specific marker molecule for CD4 + CD25 + T cells with suppressive/regulatory capacity (Treg) in the mouse. Recent studies in the human system, however, indicate that the expression of Foxp3 can be T cell activation dependent. This tempted us to evaluate the significance of Foxp3 expression under autoimmune conditions with chronic T cell activation in patients with systemic lupus erythematosus (SLE) as compared with healthy controls (HCs). Methods: Proportions of peripheral blood CD4 + Foxp3 + T cells and CD4 + CD25 high T cells were determined in patients with active and inactive SLE as compared with HC by flow cytometry. Comparative analysis of the percentage of CD4 + Foxp3 + T cells and of percentage of CD4 + CD25 high T cells with clinical disease activity and T cell activation marker molecule expression were performed. Finally, the induction of Foxp3 expression was analysed upon T cell activation in vitro. Results: Proportions of CD4 + Foxp3 + T cells were significantly increased in patients with SLE as compared with HC and a significant correlation was observed between clinical disease activity and proportions of CD4 + Foxp3 + T cells. On the other hand, proportions of CD4 + CD25 high were decreased in SLE and no correlation with a T cell activation marker expression of was observed. In addition, in vitro activation of T cells induced Foxp3 expression. Conclusions: Our data suggest that the expression of Foxp3 on CD4 + T cells in patients with SLE, at least to some extent, reflects the activation of CD4 + T cells due to underlying disease activity and does not necessarily indicate a functional regulatory T cell capacity.